2023
DOI: 10.1002/ece3.9702
|View full text |Cite
|
Sign up to set email alerts
|

Diet composition and selection of Père David's deer in Hubei Shishou Milu National Nature Reserve, China

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 144 publications
(189 reference statements)
1
3
0
Order By: Relevance
“…orientalis, with a high crude protein and low insoluble polysaccharide content (Table 2), was also identified as a beneficial food source for Père David's deer to obtain sufficient energy to survive in early winter. The RD of T. orientalis accounted for more than 10% of the total food composition, and we speculated that nutritional value factors such as crude protein, crude fat, and polysaccharides would be important factors influencing its intake by Père David's deer in winter, in line with the previous findings by Wang et al [21].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…orientalis, with a high crude protein and low insoluble polysaccharide content (Table 2), was also identified as a beneficial food source for Père David's deer to obtain sufficient energy to survive in early winter. The RD of T. orientalis accounted for more than 10% of the total food composition, and we speculated that nutritional value factors such as crude protein, crude fat, and polysaccharides would be important factors influencing its intake by Père David's deer in winter, in line with the previous findings by Wang et al [21].…”
Section: Discussionsupporting
confidence: 88%
“…Wang et al applied fecal microscopic and stable isotope analyses to investigate the staple food plants of Père David’s deer in summer and winter from three survival modes in Jiangsu Dafeng Milu National Nature Reserve [ 19 ]. Subsequently, Wang et al used stable isotope technology to analyze the diet composition of Père David’s deer in Hubei Shishou Milu National Nature Reserve [ 21 ]. The results showed that the diet was dominated by C 3 grasses in autumn and winter, identified from fur and fecal samples, whereas the summer diet was dominated by C 3 forbs, identified from muscle and liver samples [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Environmental DNA from faeces could also be analysed using high-throughput illumina-flow techniques that would allow for total dietary species number and abundance estimates from faecels (De Barba et al 2014;Deiner et al 2017). Isotope analysis of body tissues and environmental food sources could also occur (Wang et al 2023), and the findings from the continuing work of San Juan et al ( 2021) on the consequences of captive vs. wild diets on kiwi gut microbiota should be incorporated. These wilddiet discoveries should guide the food substrate choices used in the feeding experiments.…”
Section: Improving the Captive Chick Diets Macronutritionmentioning
confidence: 99%